Developing Teacher Adaptation Ability in Using Digital Technology in the Era 5.0 Collaborative at Ash-Shidiqiyah Islamic Boarding School Lawang Wetan - Annur, Saipul; Jumiati, Jumiati; Sibron, Ahmad; Adhelmi, Adhelmi; Bastomy, Bastomy; Mukti, Mukti (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This study aims to determine the development of teachers' adaptability in the use of digital technology in the 5.0 era at the Ash-Shidiqiyah Lawang Wetan Islamic Boarding School. This study uses a descriptive qualitative research type. Data collection techniques in this study are observation, interviews and documentation. Based on the results of this study, it can be concluded that the participants including leaders, educators and education personnel benefited from the training delivered by resource persons who are experts in their fields, quite high enthusiasm, which can broaden their horizons and provide a positive impact so that they can develop teachers' abilities towards the application of the use of digital technology in the 5.0 era at the Ash-Shidiqiyah Lawang Wetan Islamic Boarding School.